Fundamental of Entrepreneurship ETR 300: De Las Frutas /Nurul Adira Kamil... [et al.] - Kamil, Nurul Adira; James, Asnah; Mazlan, Mohd Firdaus; Ibrahim, Mohd Fildza (2011)
"De Las Frutas" is derived from a Spanish word and it is translated as "The Fruit" in English. The name was chosen in order to project the idea that our business is focusing on fruit-based products. It is a partnership business which consists of five members. Each partner has their contribution shares as agreed in our partnership agreement. This partnership business will be totally owned and managed by Bumiputeras. Our business activity includes selling food and beverages.